2012
DOI: 10.1016/s1473-3099(11)70244-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of drug-resistant tuberculosis

Abstract: The global emergence and spread of multidrug resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) has led to the reexamination of surgical therapy as a possible adjunctive therapy for the treatment of drug-resistant TB. We present a case of a 26-year-old HIV-seronegative patient with pulmonary XDR-TB refractory to medical therapy. Surgical resection of the patient’s solitary cavitary lesion was performed as adjunctive treatment and a successful outcome with a combination of surgery and medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 50 publications
1
64
2
5
Order By: Relevance
“…There is only one published case report evaluating SLD concentrations inside human cavitary lesions (9). Reports of worse clinical outcomes among patients with cavitary disease offer compelling but indirect evidence for low intracavitary SLD concentrations (10)(11)(12).…”
mentioning
confidence: 99%
“…There is only one published case report evaluating SLD concentrations inside human cavitary lesions (9). Reports of worse clinical outcomes among patients with cavitary disease offer compelling but indirect evidence for low intracavitary SLD concentrations (10)(11)(12).…”
mentioning
confidence: 99%
“…In reported series, selection bias by indication is a potential flaw as patients who underwent surgery were perhaps younger or in a better clinical condition. However, even with these limitations, surgical resection has been suggested early in the course of treatment of MDR-TB [8,9]. A recent meta-analysis showed that the treatment effect of surgery added to chemotherapy was more pronounced in studies with extensively drug-resistant TB.…”
mentioning
confidence: 99%
“…Its place has recently been revised. [66][67][68] In patients with a new episode of MDR-TB, unilateral lung involvement and good general condition, surgery seems to improve the outcome whereas in patients in retreatment, with XDR-TB, bilateral disease or low body mass index, the outcome is poor.…”
Section: Although These Results May Not Apply To Other Settings Partmentioning
confidence: 99%